Optimizing use of U.S. Ex-PVP inbred lines for enhancing agronomic performance of tropical Striga resistant maize inbred lines - Sayadi Maazou, A.R.; Gedil, Melaku A; Adetimirin, Victor O.; Mengesha Abera, W.; Meseka, S.K.; Ilesanmi, O.J.; Agre, A.P.; Menkir, A. (Springer, 2022)
Background Temperate maize inbred lines with expired Plant Variety Protection Act certificates (Ex-PVP) are potential sources of desirable alleles for tropical germplasm improvement. Up to now, the usefulness of the Ex-PVP inbred lines as a potential source of novel beneficial alleles for Striga hermonthica resistance breeding to enhance genetic gain in tropical maize has not been reported.